1993
DOI: 10.3109/08037059309077167
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary C-Peptide and Albumin Excretion in Juvenile Borderline Hypertensives

Abstract: The study was designed to evaluate the urinary excretion of C-peptide and albumin, and urinary N-acetyl-beta-D-glucosaminidase (NAG) activity in juvenile borderline hypertensives. The second aim was to examine the relationship between these variables and ambulatory blood pressure level and variability. The study group consisted of 21 non-obese males consecutively chosen from patients with borderline hypertension, defined by sphygmanometer readings, examined in our outpatient clinic. All subjects collected sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Increased UAE has been reported in people with altered circadian pattern of BP (non-dippers). 34 In studies the correlation was observed only in healthy people 16 or only in hypertensives. 27 The relation this study only a few persons could be classified as non-dippers.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Increased UAE has been reported in people with altered circadian pattern of BP (non-dippers). 34 In studies the correlation was observed only in healthy people 16 or only in hypertensives. 27 The relation this study only a few persons could be classified as non-dippers.…”
Section: Resultsmentioning
confidence: 98%
“…Similar to index of cardiovascular risk remains to be answered. Reports concerning the possible relationships the results of another study, 16 UAE during the night constituted only a third of 24 h-UAE. Lower UAE between albuminuria and other cardiovascular risk factors are few and inconsistent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations